2022
DOI: 10.30657/pea.2022.28.26
|View full text |Cite
|
Sign up to set email alerts
|

E-commerce and last mile delivery technologies in the European countries

Abstract: Society, companies and institutions are involved in a digital transformation that can be pervaded in various industries or sectors, and this also applies to communication, sales and distribution channels. The possibilities of e-commerce have also increased and world trade has been further developed. In 2020, more than two billion people bought goods or services over the Internet. Customer satisfaction depends on the solution of the last mile process, the method of picking up shipments as well as the time and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In a big data analysis of 54250 customer reviews of Meituan China [1], it was suggested that maintaining high levels of service at the contact point in the distribution link is a major requirement towards achieving overall customer satisfaction. Out-of-home delivery enhances the customer experience by using an automated parcel locker or machine (APM) and pick-up and drop-off delivery (PUDO) to reduce the overall cost of delivery and inventory storage in the event of a missed delivery in the European context [2]. Another study adds the aspects of delivery time window and customer satisfaction to the travelling salesman problem in the case of deliveries by unmanned aerial vehicles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a big data analysis of 54250 customer reviews of Meituan China [1], it was suggested that maintaining high levels of service at the contact point in the distribution link is a major requirement towards achieving overall customer satisfaction. Out-of-home delivery enhances the customer experience by using an automated parcel locker or machine (APM) and pick-up and drop-off delivery (PUDO) to reduce the overall cost of delivery and inventory storage in the event of a missed delivery in the European context [2]. Another study adds the aspects of delivery time window and customer satisfaction to the travelling salesman problem in the case of deliveries by unmanned aerial vehicles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subsequently, those vehicles are mostly constructed to reduce the impact on environment of the region while lessening time spent on delivery. [19]…”
Section: Choicementioning
confidence: 99%
“…Among other things, the younger generation is influenced by the desire to use greener forms of transport, both delivery with the aim of reducing environmental impact. [6], [9], [19], [20] Some advantages of drone delivery are displayed in the Table 2. There are shown some benefits as well as either possible impacts or threats of specified aspects from the perspective of authors of this paper.…”
Section: Advantages Of Last Mile For E-commercementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, e-commerce is the most common form of trade, and it is expected to be the primary sales strategy for both retail and wholesale businesses in the near future. The growing popularity and global success of e-commerce have also transformed existing support and distribution structures (Corejova et al, 2022). It allows customers to purchase goods from different parts of the world regardless of their current location.…”
Section: Introductionmentioning
confidence: 99%